Terrorist movements and the recruitment of Arab foreign fighters: a history from 1980s Afghanistan to ISIS - Warren, Roger (I.B. Tauris, 2019)
This book offers the first detailed, in-depth account of how and why some Arab foreign fighters subsequently became involved in Islamist terrorism. Drawing on a personal dataset of 3,010 Arab foreign fighters compiled using biographies, martyrdom eulogies, and postings on 'jihadi' websites, Terrorist Movements and the Recruitment of Arab Foreign Fighters suggests that the subsequent involvement in Islamist terrorism by some Arab foreign fighters is primarily forged in the crucible of defensive jihad.